Characteristics of seedling growth, physiology and inorganic ion distribution of different salt-tolerant cottons under salt stress - WANG Xiyan; QIU Boyin; LIU Yujiao; XU Xiaojian; SU Wen; ZHU Shuijin; CHEN Jinhong (浙江大学学报. 农业与生命科学版)
Salt damage is one of severe abiotic stresses which restricts yield and quality of crops all over the world. In China, saline alkali soil area is increasing mainly for environmental pollution and unreasonable fertilization in recent decades. Although cotton (Gossypium hirsutum L.) is classified as a strong salt- resistant plant, it is sensitive to salinity at seedling and flowering stages. Thus, in order to improve salt tolerance of cottons, systematical study on salt tolerance mechanism becomes more and more necessary. In other words, research on the growth and physiological characteristics can not only explore the mechanism of salt tolerance of plant, but also lay the foundation for breeding new salt-tolerant varieties.In this experiment, solution cultures with 0 (CK), 150 and 300 mmol/L NaCl were conducted to study the effect of salt stress characteristics of seedling growth, antioxidant enzyme activity, malonaldehyde (MDA) content and inorganic ion concentration two upland cotton cultivars (cv. Zaoshuchangrong7, salt- tolerant and cv. Nandanbadidahua, salt- sensitive). All the samples were collected after one week treatment. Concentrations of Na+, K+, Ca2+, and Mg2+ of different organs (root, stem and leaf) were detected by inductively coupled plasma-atomic emission spectroscopy (ICP-AES).The result showed that the salt-tolerant cotton had a larger growth quantity of root under moderate salt stress than the saltsensitive cotton. For instance, under the 150 mmol/L NaCl treatment, the salt-tolerant cv. Zaoshuchangrong7 had 14.3%, 10.9% and 21.7% more in primary lateral root number, taproot length, and root mass than the control, respectively. Also, the higher net photosynthetic rate and antioxidant enzyme activity could be maintained in the leaf of salt-tolerant cotton under the salt stress. For example, the activities of superoxide dismutase (SOD) and peroxidase (POD) were increased gradually in the salt-tolerant cv. Zaoshuchangrong7 along with the increase of salt stress, while the activities of these enzymes increased firstly and then reduced salt-sensitive cv. Nandanbadidahua. Furthermore, there was a regular distribution of inorganic ion concentrations of the salttolerant cv. Zaoshuchangrong7 under the same NaCl stress: greatly higher concentration of Na+ in the root than in the stem and leaf; higher concentrations of K+, Ca2+, and Mg2+, but lower ratio of Na+/K+ in the shoot. It was indicated that the salt-tolerant cv. Zaoshuchangrong7 could store up part of Na+ in the root thereby to relieve Na+ toxicity in the shoot. However, MDA content of salt- sensitive cv. Nandanbadidahua increased more dramatically than the salt- tolerant cv. Zaoshuchangrong7 when the NaCl concentration climbed from 150 to 300 mmol/L. Under the 150 and 300 mmol/L NaCl treatments, the MDA contents of salt-sensitive cv. Nandanbadidahua increased 30.3% and 83.5%, respectively, when compared with the control, and remained higher level than the salt-tolerant cv. Zaoshuchangrong7.To sum up, this study reveals that protection from ion toxicity and oxidative damage by regulating the root growth, enhancing the activity of antioxidant enzyme and coordinating the ion homeostasis in different organs may be major physiological mechanisms of salt-tolerant cotton in response to salt damage.